2021
DOI: 10.21834/ebpj.v6i16.2727
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Occupation-Based Intervention for Older People with Mild Dementia in the Institution

Abstract: Older people with dementia always experience the cognitive difficulties that are believed to impact their daily life significantly. However, information regarding occupation-based intervention toward older people with mild dementia in the institution is inconclusive. The results of this randomized controlled trial indicate a significant difference in cognitive functions, social relationship, and the quality of life. Participants in the experimental group improved significantly compared to the participants in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Meaningful activities/occupations were the primary intervention in four of the included studies [18][19][20][21].…”
Section: (A) Meaningful Activities/occupationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Meaningful activities/occupations were the primary intervention in four of the included studies [18][19][20][21].…”
Section: (A) Meaningful Activities/occupationsmentioning
confidence: 99%
“…Three level 1a studies were identified [9,18,30]. Twelve level 1b studies were identified [19][20][21][22][24][25][26][27][28][29]31,32]. A single level 2b study was identified [23].…”
Section: (A) Meaningful Activities/occupationsmentioning
confidence: 99%
See 2 more Smart Citations
“…As people age, their engagement in various activities may shift due to changes in health, social roles, and environment (Elder & Johnson, 2018). For older people, participating in meaningful occupations can enhance physical, mental, and social health (Ibrahim et al, 2021) leading to a more satisfying and independent lifestyle. These interventions are customised to reflect the personalised factor, cultural background, contextual and environmental settings of each individual (Christiansen & Haertl, 2023).…”
Section: Introductionmentioning
confidence: 99%